Analisis Implementasi Server Chatting pada Wireless LAN - Satra, Ramdan (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2020)
There are currently many types of social media, but all of them are based on external servers. This causes communication data between users on social media to be stored on an external server. Retrieval of data without the permission of the owner is very possible. Therefore, we need a local server to store these data in certain companies or organizations. This research consists of several stages, namely designing a chat server topology, then configuring a chat server using Kamailio and finally testing the performance of the local network with parameters delay, packet loss and wireless signal strength (decibels). The results of this study indicate that the chat server implementation can be applied to the Faculty of Computer Science UMI based on observations of delay, packet losss and signal strength on the 1st and 2nd floors. On the 1st floor, the network access is quite good. WiFi is in the position of -50 dBm to -76 dBm and 0% packet loss and delays from 8 ms - 60 ms. On the 2nd floor, the WiFi network access is good enough, but at the 2nd location point, the second floor has a long delay of 563 ms, this shows bad access to the chat server, but the whole point shows that the second server's chat access is good.